The Effect Of Leadership And Innovation On UMKM Performance Mediated By Emotional Intelligence - Linda Wahyuni; Mardiana, Mardiana; Fatimah Durry Az-Zahro; Farissa Avikass Borneta; Devi Khairunnisa; Dinda Elissa Agustina; Katharina Siswi Widyawati; Maya Fitriani; Musrefinah Lediya; Nisrina Rahmah Hayati; Yeni Oktafiani Putri (Jurnal Multidisiplin Sahombu, 2025)
The development of the Master Plan for the Development of Science and Technology (IPTEK) is a strategic step to advance Indonesia in facing the competitive era of globalization. With abundant natural and human resource potential, Indonesia is faced with challenges such as limited research budget, lack of quality human resources, and weak collaboration between research institutions, universities, and industry. This master plan is expected to provide a roadmap for innovation that is oriented towards community needs and increases the nation's competitiveness. This research is a research that uses qualitative research, namely a type of research that is guided by subjective, non-statistical and non-systematic assessments, namely assessments not in the form of numbers and scores but rather quality. This article discusses the importance of international collaboration, the development of STEM-based curriculum, and strengthening resources and infrastructure to support a sustainable innovation ecosystem. In addition, the master plan also focuses on increasing community and stakeholder participation in the development of IPTEK. The challenges faced in implementing this plan are also presented, as well as the role of public relations in building a positive image and socializing IPTEK programs to the public. In conclusion, this master plan is the key to sustainable social and economic transformation, in order to create a better future through the use of technology.